Erasmo, Maquiavel e Moro e a Modernidade: Estilos e Projetos Sociais na Filosofia Política Renascentista - Paulo Ferreira da Cunha (História - Revista da Faculdade de Letras da Universidade do Porto, 2017)
The centenaries and other similar celebrations have the “gift” of not letting erase the memory of important facts, personalities and works that the present times consider relevant. But obviously they have a great ideological footprint and promote not a little deal of trivialization, raising celebrity to the "worst of misunderstandings" as Jorge Luis Borges observed. On the contrary, in a critical perspective, we point out three giants of the political philosophy of modernity: Erasmus, Machiavelli and More, authors of three fundamental works for the "styles" of thinking politics, law and power in future times. This article also emphasizes, in its dialogue the dimensions of the social project, be it a social criticism (mainly Erasmus), be it a political treaty (specially Machiavelli), or a utopia and similar (namely More).